Implementation of a Web-Based Information System to Improve the Efficiency of Harvest Data Reporting at the Department of Agriculture, Karawang Regency - Aprilia, Eka; Hendri, Hendri; Farabi, Nur Ali; Afni, Nurul; Safitri, Rizky Ade (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
The development of information and communication technology encourages the need for a more effective data reporting system, especially in agriculture. The Department of Agriculture of Karawang Regency, as one of the main rice production centers in Indonesia, still faces several obstacles in harvest reporting, such as manual processes, reporting delays, and limited data visualization. This study aims to design and develop a web-based information system to improve the efficiency and accuracy of harvest reporting. The research method was carried out through observation and interviews for requirements analysis, followed by the application of the Rapid Application Development (RAD) approach. The result is a web-based application that enables digital data input, presents reports in table and chart formats, and provides online access according to user roles. This system is expected to accelerate the reporting process, support the digitalization of agricultural administration, and become a practical solution for the Department of Agriculture of Karawang Regency in managing real-time harvest data.